Neonatal Jaundice: Perception of Pregnant Women Attending Antenatal Clinic at a Tertiary Hospital in Southwest, Nigeria - Ogundare Ezra Olatunde; Omoyajowo Adefunke Christianah; Babatola Adefunke Olarinre; Ajite Adebukola Bidemi; Adeniyi Adewuyi Temidayo; Fatunla Odunayo Adebukola; Agaja Oyinkansola Tolulope; Taiwo Adekunle Bamidele; Oluwayemi Isaac Oludare; Olatunya Oladele Simeon (SAGE Publishing, 2020)
Background: Severe neonatal jaundice (NNJ) remains a leading cause of preventable brain damage, mental handicap, physical disabilities, and early death among infants. Methods : Using a descriptive cross-sectional study design, information was gathered using a structured, pretested questionnaire from 518 pregnant women who attended the antenatal clinic at a tertiary Hospital in Southwest Nigeria. Results : Most (77%) of the respondents have heard about NNJ prior the survey. Most respondents (69.5%) demonstrated poor knowledge of the causes of NNJ. The majority, 98.4% had good attitude toward treatment of NNJ. Most respondents (72.1%) demonstrated poor knowledge of the correct treatment of NNJ. A quarter of the respondents knew no danger sign of NNJ. Conclusion : There is serious knowledge gap among the respondents about the causes, treatment, dangers signs and complications of NNJ. There is need for increased awareness campaign using every available means of reaching women of reproductive age group to reduce the consequences of this common neonatal problem.